Ziswaf and Islamic Bank: Study of Ziswaf Fund Management at Bank Muamalat KC Darmo Surabaya - Arin Setiyowati; Achmad Syaiful Hidayat (ITB AAS INDONESIA Surakarta, 2023)
This study aims to photograph the management of Ziswaf Faunds of Bank Muamalat KC Darmo as a bridge between muzakkin and mustahik (intermediaries) to fulfill their social function obligations. Sharia social funds (ZISWAF) at Bank Muamalat KC Darmo are sourced from employees and customers of Bank Muamalat KC Darmo. From the results of the funds collected, Bank Muamalat KC Darmo will distribute social funds as a whole to be managed and distributed by the Baitul Maal Muamalat National Amil Zakat Institution (LAZNAS) which is a subsidiary of Bank Muamalat Indonesia which is engaged in ZIS and waqf. Using a Qualitative Case Study approach. Data was collected by means of interviews and in-depth documentation. The results showed that the implementation in the management of Ziswaf Funds (ZISWAF) in Bank Muamalat KC Darmo uses a conservation pattern (achieving a sufficient level of profitability and a low and high level of risk).